The MdCo gene encodes a putative 2OG-Fe (II) oxygenase that positively regulates salt tolerance in transgenic tomato and apple - Yuan, Penghao (Plant science : an international journal of experimental plant biology, 2024)
Copyright © 2024 Elsevier B.V. All rights reserved.